Impact of iron supplementation in infants in a private clinic to prevent anemia - Silva Díaz, Jaime Antero (2025)
Objectives: To determine the impact of iron supplementation in three and four month old infants to prevent anemia at the Limatambo clinic in San Juan de Lurigancho. Materials and methods: An explanatory and applicative research was conducted, with a quasi-experimental design with a comparative pre-test - post-test in two groups. Results: A total of 97 infants were studied, 51.5% of three months and 48.5% of four months, seven infants (7%) had poor adherence, and were not included in the analysis. 57% were male and 43% were female. Cesarean birth predominated (73%) at 39 weeks of gestation (42%). Exclusive breastfeeding was found in 58% and nutritional evaluation showed no differences in both groups. Anemia at six months was found in one and two infants who started iron supplementation at three and four months respectively. The average hemoglobin was 10.8 gr% and 11.7 gr% at three and four months respectively. At the end of the study, three- and four-month-old infants had an average hemoglobin of 11.8 gr%. Conclusions: Supplementation with polymaltose iron 2 mg/kg/day in three- and four-month-old infants is effective in preventing anemia at six months, and supplementation at three months of age is more effective than at four months in preventing anemia at the Limatambo clinic, San Juan de Lurigancho headquarters during November 2021-October 2022.